2015
DOI: 10.1002/adma.201503255
|View full text |Cite
|
Sign up to set email alerts
|

Highly Elastic and Conductive Human‐Based Protein Hybrid Hydrogels

Abstract: A highly elastic hybrid hydrogel of methacryloyl‐substituted recombinant human tropoelastin (MeTro) and graphene oxide (GO) nanoparticles are developed. The synergistic effect of these two materials significantly enhances both ultimate strain (250%), reversible rotation (9700°), and the fracture energy (38.8 ± 0.8 J m−2) in the hybrid network. Furthermore, improved electrical signal propagation and subsequent contraction of the muscles connected by hybrid hydrogels are observed in ex vivo tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 249 publications
(213 citation statements)
references
References 56 publications
(76 reference statements)
3
209
0
1
Order By: Relevance
“…In another study, we added GO to methacryloyl-substituted recombinant human tropoelastin (MeTro) to develop an elastic and electrically conductive biomaterial for cardiac tissue engineering (Fig. 3 (c)) [98]. The addition of GO to the MeTro matrix improved its elastic modulus by 53% and rupture strain by 45%.…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…In another study, we added GO to methacryloyl-substituted recombinant human tropoelastin (MeTro) to develop an elastic and electrically conductive biomaterial for cardiac tissue engineering (Fig. 3 (c)) [98]. The addition of GO to the MeTro matrix improved its elastic modulus by 53% and rupture strain by 45%.…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…(c-iv) Immunohistology images of MeTro/GO hydrogels after subcutaneous implantation for 28 days. (Reprinted with permission from [98] Copyright (2015) John Wiley & Sons, Inc.).…”
Section: Fig1mentioning
confidence: 99%
“…Mechanical interlocking can also be achieved by roughening or organizing the surface of the hydrogel. Xie et al showed that by forming a hydrogel fiber bundle, it is possible to form a conductive air guiding structure by coating a conductive polymer on its surface [152]. In this experiment, since there was sufficient mechanical bonding between the surface of the fiber nanoscale mat and PPy, peeling off of the coating was not indicated, and the electrochemical properties were similar to that of PPy macromolecules.…”
Section: Coating Processmentioning
confidence: 71%
“…This conductive foam is highly compressible, exhibiting linear behavior up to 70% strain with no observed hysteresis effect, and causing it to gain in popularity for use in both pressure and strain sensors [48] . More recently, Ali Khademhosseini et al integrated GO nanoparticles into a hydrogel elastomer to engineer a biocompatible and stretchable hydrogel with tunable electrical and mechanical properties [84] . The result was an electrically conductive and highly elastic MeTro/GO hybrid hydrogel, where methacry-loyl-substituted tropoelastin (MeTro) is a biocompatible elastomer (Figure 2d).…”
Section: Graphene-conjugated Compositesmentioning
confidence: 99%
“…Exploiting the characteristics of hybrid materials, such as conductivity, elasticity, transparency and piezoresistivity, has enabled the development of a variety of soft, stretchable sensors, including strain, pressure, tactile and acoustic sensors [40,68,69,80,84,139] . For instance, carbon black composites in soft elastomers led to the development of wearable piezoresistive strain sensors for taking movement and assessing skin properties.…”
Section: Applications Of Stretchable Conductive Compositesmentioning
confidence: 99%